The Influence of Financial Literacy, Lifestyle, and Social Environment on Impulsive Buying Among Generation Z, with Self-Efficacy as a Mediating Effect - Nesya Tonzani; Tajul 'Ula; Arinal Rahmati (IAI Ummul Ayman, Meureudu, Pidie Jaya, Aceh, Indonesia, 2026)
This study aims to examine the effects of financial literacy, lifestyle, and social environment on impulsive buying behavior among Generation Z in Langsa City, with self-efficacy serving as a mediating variable. An explanatory research design with a quantitative approach was employed. The study involved 200 Generation Z respondents aged 17–28 years who actively used digital shopping platforms and had online purchasing experience. A multistage sampling procedure was applied by combining purposive sampling and stratified random sampling. Data were collected through a five-point Likert-scale questionnaire and analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS) with SmartPLS 4.0. The results indicate that social environment had a positive and significant effect on impulsive buying (β = 0.654, t = 5.337, p < 0.001), whereas financial literacy (β = −0.046, t = 0.744, p = 0.457) and lifestyle (β = 0.237, t = 1.874, p = 0.061) did not significantly affect impulsive buying. Likewise, financial literacy (β = 0.361, t = 1.739, p = 0.082), lifestyle (β = −0.049, t = 0.190, p = 0.849), and social environment (β = −0.023, t = 0.085, p = 0.932) did not significantly influence self-efficacy, while self-efficacy also had no significant effect on impulsive buying (β = 0.072, t = 0.791, p = 0.429). Furthermore, the mediation analysis revealed that self-efficacy did not significantly mediate the effects of financial literacy (β = 0.026, p = 0.494), lifestyle (β = −0.004, p = 0.897), and social environment (β = −0.002, p = 0.953) on impulsive buying. The structural model explained 72.2% of the variance in impulsive buying (R² = 0.722), while social environment demonstrated the largest effect size (f² = 0.627). These findings suggest that impulsive buying among Generation Z is primarily shaped by external social influences rather than financial literacy or self-efficacy. From the perspective of Islamic financial management, the findings may serve as an ethical basis for strengthening responsible consumption behavior and financial decision-making, although Islamic financial literacy and Islamic consumption constructs were not directly measured in this study.